2008
DOI: 10.1159/000150315
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Exercise Training as Maintenance after Outpatient Pulmonary Rehabilitation

Abstract: Background: Pulmonary rehabilitation is successful in improving exercise capacity and quality of life in patients with chronic obstructive pulmonary disease (COPD). However, training effects diminish over time. Objectives:We evaluated the effects of simple, daily, structured, self-monitored, home-based exercise training for patients with moderate COPD after a 3-week outpatient rehabilitation. Methods: We conducted a randomized, controlled, observer-blind trial. Twenty patients were recruited. Ten patients perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(101 citation statements)
references
References 51 publications
4
84
2
11
Order By: Relevance
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Thirteen studies were done in Europe 17,19,21,31,33,38,42,43,45,46,48,49,50 , six in Asia 30,36,39,40,44,47 , two in Australasia 34,35 , one in North America 41 , and one in South America 32 . Among the studies included in the review, 19 17,18,19,30,31,32,33,34,36,38,39,40,42,43,44,46,47,48,49,50 compared HCPR to control group (n = total 893; n HCPR = 485), while four 35,37,41,45 compared HCPR to OPR (n total = 375; n HCPR = 178). No studies reported harmful effects related to HCPR during interventions.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the behavior of these variables is not yet fully clarified for resistance training with the use of elastic tubing 24 .…”
Section: Introductionmentioning
confidence: 99%